Fundamentals of ballistics for the treatment of firearms injuries in reconstructive surgery - P. de León, Miguel A.; Ortega, Julio A.; G. Santos, Leonardo; López, Francisco; Pérez, Rocio (International Journal of Research in Medical Sciences, 2025)
Firearm injuries constitute a significant global public health challenge, whit more than one billion firearms in circulation and an estimated 600 daily fatalities. This review explores fundamental ballistics concepts and their relevance to injury mechanisms. It highlights the critical role of kinetic energy and projectile behaviour, such as velocity, trajectory, and design, in determining injury severity. High velocity firearms, expanding bullets, and shotgun shells create complex injury patterns, emphasizing the emphasizing the importance of distinguishing between permanent and temporary cavities during clinical assessment. The knowledge of ballistic principles is indispensable for plastic and reconstructive surgeons managing firearm injuries. Understanding projectile and tissue interactions informs precise surgical planning for soft tissue and bone reconstruction, enhancing patient outcomes. This expertise is essential in addressing the rising number of firearm related cases in region whit prevalent armed violence such as Mexico. Continuous integration and updating of ballistic knowledge in surgical practices are vital to improving care and minimizing long term sequelae in affected patients.